2015
DOI: 10.1590/s0034-8910.2015049005886
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus in Brazil’s inmate population: a systematic review

Abstract: OBJECTIVE To estimate the prevalence of hepatitis C virus infection in Brazil’s inmate population.METHODS Systematic review on hepatitis C virus infection in the inmate population. Brazilian studies published from January 1, 1989 to February 20, 2014 were evaluated. The methodological quality of the studies was assessed using a scale of 0 to 8 points.RESULTS Eleven eligible studies were analyzed and provided data on hepatitis C virus infection among 4,375 inmates from seven states of Brazil, with a mean qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
0
18
1
5
Order By: Relevance
“…In Brazil, a systematic review published in 2015 showed that the average prevalence of HCV was 13.6% among Brazilian prisoners, varying between 1.0% and 41.0% and being the lowest in the state of Espírito Santo and highest in São Paulo. However, a meta-analysis of the risk factors associated with the prevalence of HCV in Brazilian prisons could not be performed because most studies did not analyze the risk factors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a systematic review published in 2015 showed that the average prevalence of HCV was 13.6% among Brazilian prisoners, varying between 1.0% and 41.0% and being the lowest in the state of Espírito Santo and highest in São Paulo. However, a meta-analysis of the risk factors associated with the prevalence of HCV in Brazilian prisons could not be performed because most studies did not analyze the risk factors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of HBV and HCV is mainly related to blood contamination due to injecting drug use, formerly due to contaminated blood transfusion. Sexual intercourse is still somewhat controversial in HCV transmission, with conflicting data in the literature, while in HBV transmission its role has already been proven 6,[22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…As taxas de prevalência na África, América, Europa e Sudeste da Ásia é de aproximadamente 2,5% (Marinaki et al, 2015). A hepatite por si só vem contaminando muitas pessoas no Brasil, sendo responsável pela enfermidade hepática aguda e crônica, principalmente as que se encontram em locais de fácil contaminação, tais como o sistema carcerário brasileiro (Magri et al, 2015), trabalhadores do setor de saúde (Assunção et al, 2012). Internacionalmente, a hepatite viral C é responsável por 60% dos casos de doença hepática crônica na Índia (Thakur et al, 2010), bem como em Portugal ocupa o segundo lugar entre as causas de doenças do fígado (Mota et al, 2010).…”
Section: Revista De Gestão Em Sistemas De Saúde -Rgssunclassified